Evaluation of Drug Management Before and During the COVID-19 Pandemic In The Pharmaceutical Installation of NTB Provincial Hospital - Wisnu, M. Ari; Khairani, Ayudia Cipta (Journal of Islamic Pharmacy, 2025)
The COVID-19 pandemic that occurred from 2019 to 2023 and has spread to nearly 190 countries in the world has caused a shortage of drug supply. The need for public medicines that must be available for health services makes hospitals must try to fulfill and currently, the COVID-19 pandemic situation is continuing so hospitals must be ready to provide health services to patients. This study aims to evaluate drug management in the Pharmacy Installation of the NTB Provincial Hospital before the COVID-19 pandemic in 2019 and during the COVID-19 pandemic in 2020. This study used a descriptive-evaluative method. The main data was collected through documents containing specific data on drug management history. Supporting data was collected through interviews with the pharmaceutical installation. The results of the suitability of drug management in the Pharmacy Installation of the NTB Provincial Hospital before the COVID-19 pandemic in 2019 obtained 5 indicators that did not meet the standards and 6 indicators that met the standards while during the COVID-19 pandemic in 2020 there were 7 indicators that did not meet the standards and 4 indicators that met the standards.